2017
DOI: 10.1007/s00253-017-8269-6
|View full text |Cite
|
Sign up to set email alerts
|

RDX degradation in bioaugmented model aquifer columns under aerobic and low oxygen conditions

Abstract: Degradation of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) in laboratory columns following biostimulation and bioaugmentation was investigated using sediment and groundwater from a contaminated aquifer at a US Navy facility. No RDX degradation was observed following aerobic biostimulation with either fructose or lactate (both 0.1 mM) prior to bioaugmentation. Replicate columns were then bioaugmented with either Gordonia sp. KTR9, Pseudomonas fluorescens I-C (Ps I-C), or both strains. Under aerobic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although many RDX bioremediation studies have focused on biostimulation with an organic donor, recent studies have turned to bioaugmentation as an alternative bioremediation method to address the wide variety of site characteristics and the low cleanup goals for RDX. Initial bioaugmentation studies involved addition of aerobic RDXdegrading microbes (Crocker et al, 2015;Fuller et al, 2015Fuller et al, , 2017Michalsen et al, 2016). Achieving and maintaining aerobic conditions may be difficult in many contaminant plumes, however, especially when an organic donor source also needs to be added to support aerobic degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many RDX bioremediation studies have focused on biostimulation with an organic donor, recent studies have turned to bioaugmentation as an alternative bioremediation method to address the wide variety of site characteristics and the low cleanup goals for RDX. Initial bioaugmentation studies involved addition of aerobic RDXdegrading microbes (Crocker et al, 2015;Fuller et al, 2015Fuller et al, , 2017Michalsen et al, 2016). Achieving and maintaining aerobic conditions may be difficult in many contaminant plumes, however, especially when an organic donor source also needs to be added to support aerobic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving and maintaining aerobic conditions may be difficult in many contaminant plumes, however, especially when an organic donor source also needs to be added to support aerobic degradation. Recent laboratory tests (Fuller et al, 2017) and a field test (Michalsen et al, 2020) used bioaugmentation with a combined inoculation of the aerobic RDX-degrading microbial species, Gordonia sp. KTR9, and a facultative RDX-degrading strain, Pseudomonas fluorescens strain I-C cells ("Strain I-C ′′ ) for degradation of RDX, without the presence of nitrate or perchlorate co-contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Despite encouraging initial results, both bacterial numbers of Gordonia sp. KTR9 and xplA levels declined over time (Crocker et al 2015;Michalsen et al 2016;Fuller et al 2017). Factors preventing the accumulation of sufficient numbers of xplAB-containing soil bacteria to remove RDX-contamination, preventing downstream contamination are unknown, but xplAB-engineered plant endophytic, and associated rhizospheric bacterial communities indigenous to a contaminated site would be predicted to successfully reestablish in that environment.…”
Section: Endophytic and Rhizospheric Communitiesmentioning
confidence: 99%
“…Because the aerobic degradation of RDX does not produce toxic intermediates, the use of RDX-degrading strains, such as Gordonia KTR9, has been tested for the bioremediation of polluted water [ 27 , 28 , 29 ]. Those studies showed that in situ bioaugmentation and biostimulation of aerobic bacteria lead to rapid degradation of RDX in a polluted aquifer over a long period [ 30 ].…”
Section: Introductionmentioning
confidence: 99%